STATE REGULATION OF DEVELOPMENT OF INNOVATION PROCESSES IN THE FIELD OF AGRICULTURAL ECONOMY AND LAND RELATIONS - Shportyuk, Natalia (Theory and Practice of Public Administration, 2019)
The article considers the importance of innovative development of the Ukrainian agroindustrial complex as an indispensable condition for competitiveness in the agrofood market. The theoretical foundations of the sectoral innovation system of agroindustrial complex, the current state of innovative development of the agrarian sphere, including state regulation and informational and consulting support are revealed. The article gives a detailed analysis of the main directions of the development of innovative processes in the field of agribusiness and land relations, and provides practical recommendations for improving the efficiency of innovative activity in agroindustrial production. The purpose of the article is to develop theoretical and methodological principles and practical recommendations for improving the efficiency of innovative activity in agroindustrial production. In the field of agribusiness and land relations it is expedient to distinguish the following main directions of development of innovation processes: Ensuring the development and implementation of agrarian policy in Ukraine for the long-term, adequate process of globalization. Improvement of organizational and economic mechanism of functioning of agroindustry complex with the purpose of creation of highly developed sustainable agricultural production. Development of the methodology of forming an organizational and economic mechanism for the development of industries and forms of management in the agroindustrial complex. Formation of perspective models of markets for raw materials, food and material and technical resources. Development of the forecast of development of agroindustrial complex for a long-term perspective Development of informatization and computerization of production and implementation of innovative management methods. Development and implementation of investment and innovation policy, which provides enhanced reproduction in the industry Implementation of scientifically grounded program of development of rural territories with the decision of the whole complex of issues of social settlement of the village. Implementation in practice of a clear organizational and economic mechanism for the development and regulation of land relations in agriculture. At the present stage of development of the agrarian economy, increasing the efficiency of agricultural production, the acceleration of scientific and technological progress, the determining role in which the innovation activity belongs, the creation of innovative products and their implementation in agrarian production, is of paramount importance. However, the achievements of scientific and technological progress are not yet organically included in the implementation of socio-economic and technological and technological processes of agricultural production and other branches of the agroindustrial complex. The weak link remains the organization of wide application in the field of scientific developments, creation of conditions for increasing the economic interest of economic entities in the use of innovative products. This is determined by the relevance of the research topic, the scientific significance and the practical value of the results obtained.